2016
DOI: 10.1111/edt.12281
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for traumatic dental injuries in the primary dentition: concepts, interpretation, and evidence

Abstract: The purpose of this comprehensive review is to explore the main concepts related to quantification and interpretation of risk factors and investigate characteristics associated with traumatic dental injuries (TDI) in the primary dentition. Initially, the main concepts related to causality and risk factors were summarized, including how to measure, express, and compare risk as well as interpret statistical significance. Based on a structured search through PubMed, original research articles regarding TDI and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 55 publications
0
31
1
3
Order By: Relevance
“…However, this association is only consistent for older age groups, in which behavioral differences between genders are more evident. Although a statistically significant difference was found in the present study, it may not be clinically relevant, as it may not be large enough to warrant greater care or orientations given to the parents of male preschoolers …”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…However, this association is only consistent for older age groups, in which behavioral differences between genders are more evident. Although a statistically significant difference was found in the present study, it may not be clinically relevant, as it may not be large enough to warrant greater care or orientations given to the parents of male preschoolers …”
Section: Discussioncontrasting
confidence: 61%
“…Although a statistically significant difference was found in the present study, it may not be clinically relevant, as it may not be large enough to warrant greater care or orientations given to the parents of male preschoolers. 4 This study has limitations that should be considered. The considerable proportion of dropouts during the follow up may have influenced the results in an unknown manner.…”
Section: Come Few Studies Have Investigated Associations Between Antmentioning
confidence: 94%
See 1 more Smart Citation
“…Studies reporting the epidemiologic data on TDI are limited to the information obtained from cross‐sectional and prospective studies and the methodology on how the information is gathered is not clear . For example, the prevalence of TDI in the primary dentition ranges between 6.2% and 47% in the literature . Shekhar et al reported a prevalence of 6.2% in India .…”
Section: Introductionmentioning
confidence: 99%
“…1,5,7 For example, the prevalence of TDI in the primary dentition ranges between 6.2% and 47% in the literature. 12 Shekhar et al reported a prevalence of 6.2% in India. 13 A study on 1-to 3-year-old children on previous TDI experience during a vaccination campaign was reported as 41.6%, 14 whereas it was even higher as 60.5% when radiographic evaluation was included.…”
mentioning
confidence: 99%